Práticas de governança corporativa diferenciadas e desempenho: um estudo aplicado em empresas do novo mercado da BMFBovespa - Sousa, Rogério Alexandre Gonçalves de (2011)
With the growing importance of companies in society, the agency relationship is no longer restricted to the shareholders and managers, the community as a whole, employees, customers, government, potential investors, become part of this relationship, demanding the company also meets their interest. In response to this situation, comes the concept of corporate governance, which is a set of practices that intends through principles such as transparency and respect to the diverse stakeholders in the company situation, to minimize the conflict of interest derived from an agency relationship. There are several agencies aimed at the development of corporate governance as the Brazilian Institute of Corporate Governance and the Organization Economic Cooperation and Development, who make recommendations about what they consider good corporate governance practices and even the São Paulo Stock Exchange BMFBovespa created since the year 2000 different levels of trading in accordance with the degree of governance practices adopted by these companies. The highest degree considered by BMFBovespa is New Market, which serves as the basis for study. About the companies that comprise the New Market was rated a set of not mandatory practices and if these practices are connected to the companies performances. To validate this hypothesis were correlated performance indicators such as EBITDA Margin, ROA, ROI and ROE with the level of corporate governance practices. Could not be established in this study the link between best corporate governance practices and better corporate performance, however, the improvement of governance practices is an irreversible process for the relevance of the concept and its acceptance by the market